Birds of Shivapuri Nagarjun National Park, Nepal - Poudyal, Laxman Prasad; Ghimire, Manshanta; Acharya, Sanjib; Chaudhary, Hathan; Baral, Hem Sagar (Nepalese Journal of Zoology, 2024)
Shivapuri Nagarjun National Park harbors diverse avifauna. The last checklist of birds for Shivapuri, published by SNP and BCN (2007), covered 318 species. However, it excluded the Nagarjun Forest birds as this area wasn't incorporated into the national park until 2009. Since then, many new bird sightings have been reported in Shivapuri Nagarjun National Park (SNNP). To address this gap, we've compiled a comprehensive checklist of SNNP birds in Nepal's central mid-hills, drawing on direct observations and a literature review. A total of 396 species of birds belonging to 18 orders and 71 families were known to occur in the park. Order Passeriformes (n=260, 65%) and family Muscicapidae (n=50, 12%) have the highest record of the number of species. Out of 396 bird species, 237 species were recorded during the recent survey of 2021–2022 and 159 species were considered from the past literatures. 10.60% (n=42) of the recorded bird species are classified as nationally threatened according to Nepal’s national red list and 2% (n=8) are listed as globally threatened. The globally threatened birds include Vulnerable greater spotted eagle Aquila clanga, imperial eagle Aquila heliaca, and Kashmir flycatcher Ficedula subrubra; Endangered steppe eagle Aquila nipalensis and Pallas’s fish eagle Haliaeetus leucoryphus; and Critically Endangered white-rumped vulture Gyps bengalensis, slender-billed vulture Gyps tenuirostris and red-headed vulture Sarcogyps calvus. A total of 55 species recorded are included in the CITES Appendices; one species is also listed in the National Parks and Wildlife Conservation Act (NPWCA) Schedule I, and the park includes spiny babbler Acanthoptila nipalensis the only endemic bird of Nepal. Resident species make up the majority (n=243, 61.36%) of birds recorded in the national park. The remaining are the migrants which include summer and winter visitors, passage migrants and vagrants.